Pengaruh Ukuran Organisasi, Kemampuan Teknik Personal, Programipelatihan dan Pendidikan Terhadap Kinerja Sistem Informasi Akuntansi pada BPR di Kabupaten Gianyar - Ni Putu Sintya Pratiwi; Ida I Dewa Ayu Manik Sastri; Putu Gede Wisnu Permana Kawisana (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2020)
Accounting information systems are used to regulate the management of accounting data within the company, where later the data can be used as information that will be needed by the company. The purpose of this research is to determine the effect of variable organizational size, personal technical skills and training and education programs on the performance of accounting information systems at BPRs in Gianyar Regency. This research was conducted in 11 BPRs in Gianyar Regency, with a sample of 70 respondents. The data of this study were collected using a questionnaire, and the data were analyzed using multiple regression analysis. The results of this study indicate that organizational size, personal technical abilities, training and education programs have a positive effect on the performance of the accounting information system at BPRs in Gianyar Regency.